The Secret to Receive More Citation in the Field of Orthopedics and Traumatology - Şahin, Erdem; Karaismailoğlu, Bedri; Özşahin, Mahmut Kürşat; Davulcu, Cumhur Deniz; Tütüncü, Mehmed Nuri; Şeker, Ali (Cerrahpaşa Medical Journal, 2022)
Objective: The number of citations is used to determine the relative importance of an article, but there is limited information about the possible factors affecting the citation numbers in the field of orthopedics. Acta Orthopaedica et Traumatologica Turcica (AOTT) is one of the most prestigious orthopedic journals published in Turkey, which is also the official publication of the Turkish Association of Orthopaedics and Traumatology and the Turkish Society of Orthopaedics and Traumatology. This study aimed to identify and analyze the 50 most cited articles in Acta Orthopaedica et Traumatologica Turcica to determine the factors which might have an effect on citation numbers in the field of orthopedics and traumatology. Methods: The studies published in Acta Orthopaedica et Traumatologica Turcica between January 2008 and December 2020 were examined and the 50 most-cited studies were revealed. The articles were searched using the database of Web of Science Core Collection. The citation density which is defined as the citation number per year was calculated. The articles were classified by study design and the field of study. The parameters such as the level of evidence, country of origin, and the field of the first author were investigated to determine whether they have any effect on the citation numbers of an article. Results: A total of 1311 articles were reviewed. The most-cited 50 papers included 44 clinical studies, 5 basic science studies, and 1 bibliometric study. The highest number of citations in the list was 71, while the highest citation density was 7.8. The articles with level 1 evidence had significantly higher citation numbers and density (P < .001). The studies conducted by non-orthopedic researchers received significantly higher citation numbers (P = .005) and density (P = .012). The field of study or country of origin did not have a significant effect on citation numbers. Conclusion: High level of evidence provided significantly higher citation density, pointing out the need for well-designed studies. The articles from non-orthopedic researchers had significantly higher citation numbers and density compared to the articles with an orthopedic surgeon as the first author, indicating the importance of multidisciplinary work in the field of orthopedics and traumatology. Cite this article as: Şahin E, Karaismailoğlu B, Özşahin MK, Davulcu CD, Tütüncü MN, Şeker A. The secret to receive more citation in the field of orthopedics and traumatology. Cerrahpaşa Med J. October 12, 2022;46(3):201-207.